NUOVA LOCALITA' FOSSILIFERA A TEREBRATULIDAE (BRACHIOPODA) DEL TITONICO SUPERIORE NEL GRUPPO DELLE TOFANE (BELLUNO) (Rivista italiana di Paleontologia e Stratigrafia, 2020)
The present paper is dedicated to a new Terebratulidae locality within a Upper Tithonian unit (Biancone s.l.) near Cortina d'Ampezzo. The investigated area is the Tofane Mountains (Third or Inner Tofana). Terebratulidae come from a biomicrite holding rare planktonic Foraminifera and Tintinnids; Calpionella alpina Lorenz and Crassicollaria cf. intermedia (Durand—Delga) suggest an Upper Tithonian age.The megafauna consists of Terebratulidae only; borings and epizooic organisms are totally missing. The fossils are rather well preserved; they are extremely frequent and build up a Terebratula Bed.Three species belonging to the genus Tropeothyris Smirnova, 1972, have been identified, all represented by many specimens juvenile as well. Two species are new to Science: Tropeothyris francescoi SP. n. and Tropeothyris tofanensis SP. n.